STRATEGI GURU PAUD DALAM MENGELOLA KELAS DI TK ISLAM AL-AZHAR CAIRO BANDA ACEH - Zahratul Fitria; Israwati .; Dina Amalia; Suhartati .; Siti Naila Fauzia (Jurnal Ilmiah Mahasiswa Pendidikan Anak Usia Dini, 2022)
Keywords: The teacher's strategy, Administering the classThe teacher's strategy in administering the class is a procedure that teachers use to do management in the classroom that includes both the layout of the room and the organizing of learners according to a planned need and program that can help accomplish optimal learning. The purpose of this research is to describe the strategy of teacher abalone managing the class at The Islamic Kindergarten of Al-Azhar Cairo day. The study employs a qualitative approach with a descriptive type of research. Data collection techniques of observation and interview. The subject of research is three teachers at The Islamic Kindergarten of Al-Azhar Cairo day. The object of this research is teacher abalone strategy for administering the class at The Islamic Kindergarten of Al-Azhar Cairo day. Research indicates that the teacher's strategy in the management of the classes at Kindergarten of Islam Al-Azhar Cairo day consists of: a teacher's strategy in the use of classroom walls conducted by teachers, a teacher's strategy in arranging the classroom, a teacher's strategy in keeping the class clean and neat, the teacher's strategy in storing materials and learning equipment, the teacher's strategy in placing classroom limits, and the teacher's strategy in dealing with classroom nomencs.Abstrak. Strategi guru dalam mengelola kelas adalah suatu prosedur yang digunakan guru untuk melakukan pengelolaan di dalam kelas yang meliputi penataan ruangan maupun pengorganisasian peserta didik yang sesuai dengan kebutuhan dan program yang direncanakan yang dapat membantu pencapaian pembelajaran yang optimal. Tujuan penelitian ini untuk mendeskripsikan strategi guru PAUD dalam mengelola kelas di TK Islam Al-Azhar Cairo Banda Aceh. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Teknik pengumpulan data berupa observasi dan wawancara. Subjek penelitian adalah 3 guru di TK Islam Al-Azhar Cairo Banda Aceh. Objek dalam penelitian ini adalah strategi guru PAUD dalam mengelola kelas di TK Islam Al-Azhar Cairo Banda Aceh. Hasil penelitian menunjukkan bahwa strategi guru dalam pengelolaan kelas di TK Islam Al-Azhar Cairo Banda Aceh terdiri dari: strategi guru dalam pemanfaatan dinding kelas yang dilakukan oleh guru, strategi guru dalam menata ruang kelas, strategi guru dalam menjaga kelas agar bersih dan rapi, strategi guru dalam menyimpan bahan dan perlengkapan belajar, strategi guru dalam menempatkan pembatas kelas, serta strategi guru dalam mengatasi kelas yang bising.Kata Kunci: Strategi Guru, Pengelolaan Kelas